LOW-PERCENTAGE Со/CLAY CATALYSTS IN THE PROCESS OF OXIDATIVE CONVERSION OF C3-C4 SATURATED HYDROCARBONS - Massalimova Bakytgul Kabykenovna,; Jetpіsbayeva Gulіm Danebaevn,; Altynbekova Dіnara Tansykovna,; Naurzkulova Symbat Muratbekovna,; Atakozhaeva Aygul Amalbekovna ,; Sadykov Vladіslav Aleksandrovіch, (Academic Scientific Journal of Chemistry, 2019)
Oxidative conversion of C3-C4 hydrocarbons by air to oxygen-containing compounds at T = 400- 550°C and space velocity of 7500 h-1, 9000h-1 on monoxide catalysts containing 1-, 3-, 5% Сo supported on natural red clays was studied. The reaction temperature, contact time, change in the space velocity in the process of partial oxidation of C3-C4 hydrocarbons have been studied. Acid treatment of the sorbents contributed to the development of the surface area and the enlargement of pore radius, which led to an increase of oxygen-containing compounds in the final product. The SiO2/Al2O3 ratio (silica modulus) was increased after acid treatment too.